Oral bioavailability of ketoprofen in suspension and solution formulations in rats: the influence of poloxamer 188 - Fischer, Sarah Maud; Parmentier, Johannes; Reimold, Isolde; Fricker, Gert (Journal of pharmacy and pharmacology, 2012)
Objectives The aim of the current study was to investigate the effect of poloxamer 188 (P-188) on the bioavailability of the BCS class 2 drug ketoprofen in vivo. Methods Aqueous suspension and solution formulations of ketoprofen with and without P-188 were orally administered to fasted male Wistar rats. The intrinsic dissolution rate and solubility of ketoprofen in simulated intestinal fluid, in both the presence and absence of P-188, was measured. Key findings The AUC and Cmax were found to be significantly enhanced when ketoprofen was administered as suspension and P-188 was present in the formulation (Susp P-188) as compared to the surfactant-free formulation (∼4-fold higher AUC, 7-fold higher Cmax). While drug solubility appeared to be almost unaffected by P-188, a significantly faster dissolution was observed. In addition, the influence of P-188 on the drug absorption process was investigated by comparison of solution formulations with and without P-188. Conclusions The in-vivo performance of these solutions, a pure buffer solution and a P-188-containing buffer solution showed no significant difference, suggesting that the increase in bioavailability for Susp P-188 was primarily a consequence of the dissolution rate-enhancing effect.